Anaemia of rheumatoid arthritis: serum erythropoietin concentrations and red cell distribution width in relation to iron status. Issue 6 (June 1990) - Nielsen, O J; Andersen, L S; Ludwigsen, E; Bouchelouche, P; Hansen, T M; Birgens, H; Hansen, N E
Abstract : Immunoreactive serum erythropoietin concentrations were measured in 35 patients with anaemia associated with active rheumatoid arthritis. Based on an evaluation of stainable iron in the bone marrow (marrow iron grade 0-4) and serum ferritin concentrations (concentrations less than or equal to 60 micrograms/l compatible with iron deficiency) the anaemia was found to be complicated by iron deficiency in 19/35 (54%) of the patients. The mean serum erythropoietin level (57.6 (SD) 27.3) U/l) was sufficiently raised for the degree of anaemia irrespective of the size of the marrow iron stores. Thus the data do not support the contention that suppressed secretion of erythropoietin is involved in the pathogenesis of anaemia of chronic disorders. There was a significant inverse correlation between the haemoglobin concentration and log serum erythropoietin in the patients with rheumatoid arthritis. In the patients with adequate iron stores, but not in the iron depleted patients, there was a tendency for serum erythropoietin concentrations to correlate positively both with C reactive protein and erythrocyte sedimentation rate. Red cell distribution width (mean (SD) 16.3 (1.8)%) was above normal (11.5-14.5%) both in the iron replete and the iron depleted patients, and the mean red cell distribution width values did not differ significantly among the two subpopulations. The plasma lactoferrin concentration (mean (SD) 137.6 (109.9) micrograms/l) was normal and did not differ significantly between the iron deficient patients and those with adequate iron.